1997
DOI: 10.1063/1.365574
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism and electrical properties of metallic films deposited on silicone oil surfaces

Abstract: Influences of rapid annealing and substrate temperature on the magnetic properties of Co-Fe-V films J. Appl. Phys. 99, 08F105 (2006); 10.1063/1.2165590 Microstructural comparisons of ultrathin Cu films deposited by ion-beam and dc-magnetron sputtering J. Appl. Phys. 97, 093301 (2005); 10.1063/1.1886275 Electrical and microstructural characterization of molybdenum tungsten electrodes using a combinatorial thin film sputtering technique J. Appl. Phys. 97, 054906 (2005); 10.1063/1.1855395 Phase transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Based on these ideas, we subsequently present our novel approach for the plasma processing of liquids allowing not only the formation but simultaneous functionalization of thin films on liquid substrates. The first attempt to coat liquids was made by Ye et al, who successfully deposited continuous metallic films on silicone oil by RF magnetron sputtering and investigated the nucleation and growth mechanisms taking place during film formation [ 1 , 2 , 3 ]. Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these ideas, we subsequently present our novel approach for the plasma processing of liquids allowing not only the formation but simultaneous functionalization of thin films on liquid substrates. The first attempt to coat liquids was made by Ye et al, who successfully deposited continuous metallic films on silicone oil by RF magnetron sputtering and investigated the nucleation and growth mechanisms taking place during film formation [ 1 , 2 , 3 ]. Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It is unanimously reported that a multi-step formation mechanism occurs when depositing metals on liquids [ 1 , 2 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 21 , 23 , 24 , 25 , 26 ]. First, nucleation and growth of smaller clusters can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SoL, most of the works were carried out in DC mode. RF power supplies were used for the production of Au [167], Pt [168], and Pt/Ni [169] NPs and Ag films [170][171][172].…”
Section: Type Of Sputtering Plasmamentioning
confidence: 99%
“…[4][5][6][7][8] The experiments show that the films deposited on the liquid substrates may exhibit characteristic surface morphologies and plentiful physical properties. 5,6,[9][10][11] All the anomalous properties of these free sustained films are closely related to liquid substrates surfaces, because the surface types define the physical properties of objects including internal stress, interaction among the atoms, friction, collision and so on. 5,12,13) Ionic liquids are known as a salt in the liquid state.…”
Section: Introductionmentioning
confidence: 99%